RANCANG BANGUN SISTEM PRESENSI KARYAWAN BERBASIS WEBSITE TOKO IKA MUKTI PATI - Tiyas widiastuti; Sri Huning Anwariningsih; Firdhaus Hari Syahputra (Fakultas Sains, Teknologi dan Kesehatan Universitas Sahid Surakarta, 2022)
An employee attendance system is a system that performs the attendance, checks attendance data recapitulation, and recapitulation employee payroll. The employee attendance system is expected to assist employees in performing attendance and assist Ika Mukti Stores in recapitulating employee attendance and making it easier for shop owners to calculate employee salaries. This study used the waterfall method as a system development method, and data collection techniques used literature study, interviews, and document analysis. System analysis and design implemented Unified Modeling Language (UML). The system testing method used the webqual 4.0 method measures the website covering system usability and quality as well as the user satisfaction method. It is measured by a user satisfaction survey using a questionnaire instrument from respondents, namely 7 employees, 1 shop owner, and 22 general respondents. There are 2 actors in this attendance system program which include the admin or shop owner and employees. This system login uses a username and password to start the attendance system. The admin has web access to manage employee data, check employee attendance recapitulation, and manage employee payroll. The employees have web access to make attendance and check their attendance recap. This presence system also produces information about employee attendance with a one click system that makes it easier for employees to make attendance and for shop owners to calculate employee payroll data. The results of the test show that the usability quality of the presence system website is easy to use, and the display design of this attendance system is also quite attractive. Regarding the quality of information, this presence system provides information that is easily understood by users and is quite complete. In terms of service interaction quality, the presence system is sufficient to provide convenience for employees in attendance. On all assessments, users are quite satisfied with the performance of the attendance system. The results of multiple linear regression testing indicate that the quality of the usability of the website has a reasonably attractive appearance, but some features are felt to be lacking, the quality of website information is quite complete and easy to understand, and the quality of user interaction with the website is sufficient to provide employee convenience. The results of the determinant coefficient test show the number 0.84 or 84%. It means that the user is helped by the employee presence system.